Augmenting the immersed boundary method with Radial Basis Functions (RBFs) for the modeling of platelets in hemodynamic flows. (14th July 2015) - Shankar, Varun; Wright, Grady B.; Kirby, Robert M.; Fogelson, Aaron L.
Summary We present a new computational method by extending the immersed boundary (IB) method with a geometric model based on parametric radial basis function (RBF) interpolation of the Lagrangian structures. Our specific motivation is the modeling of platelets in hemodynamic flows, although we anticipate that our method will be useful in other applications involving surface elasticity. The efficacy of our new RBF‐IB method is shown through a series of numerical experiments. Specifically, we test the convergence of our method and compare our method with the traditional IB method in terms of computational cost, maximum stable time‐step size, and volume loss. We conclude that the RBF‐IB method has advantages over the traditional IB method and is well‐suited for modeling of platelets in hemodynamic flows. Copyright © 2015 John Wiley & Sons, Ltd.